Amanah Khalifah dan Perilaku Lingkungan: Peran Rasa Bersalah sebagai Mekanisme Psikologis - Nabiella Hasna Halisa; Safrina Pulungan; Syahira Amanda Zamia; Ahmad Sulaiman (Psychospiritual: Journal of Trends in Islamic Psychological Research, 2026)
Environmentally friendly behaviors is a critical component of environmental sustainability. This study aims to examine the influence of stewardship belief on pro-environmental behaviors, with environmental guilt as a mediating variable. A quantitative approach was employed using a survey method to collect data from respondents. The results indicate that stewardship belief has a positive and significant effect on pro-environmental behaviour (β = 0.758, p < 0.001) and environmental guilt (β = 0.537, p < 0.001). Environmental guilt also has a positive effect on pro-environmental behaviour (β = 0.264, p = 0.008). Mediation analysis further reveals that environmental guilt partially mediates the relationship between stewardship belief and pro-environmental behaviors, indicating the presence of both cognitive (belief-based) and affective (emotion-based) pathways in shaping behaviors. These findings highlight the importance of integrating moral beliefs and emotional responses in promoting environmentally responsible behaviors.